Cuba y la cuestión de los derechos humanos: De la representación mediática a la realidad factual - Salim Lamrani (Études Caribéennes)
Since 1959 and the advent of the Cuban Revolution, and especially since 1991 and the fall of the Soviet Union, Cuba has invariably been indicted on the issue of human rights. There is a widespread consensus among public opinion, especially in the West, to associate the island with human rights violations. Without seeking to deny the possible violations of fundamental rights that may occur in Cuban society, it is appropriate to ask whether there is a correlation between the extent of the violations of human rights identified by international institutions in a particular country and the media exposure it receives. To answer this question, this work proposes to carry out a comparative study, based on Amnesty International’s latest annual report, between four countries: Cuba, the United States, France and Spain.